Integrasi etnomatematika dalam kurikulum sekolah - Hidayah, Miftahul (Maliki Interdisciplinary Journal, 2025)
This study is a qualitative descriptive research using a literature review and exploration of empirical data from various ethnomathematical studies in Indonesia. The purpose of this study is to analyze the integration of ethnomathematics into the school curriculum as a contextual approach relevant to local cultural values. Data sources include scientific articles, field research results, and education policy documents. The results show that ethnomathematics can enhance students’ learning motivation, conceptual understanding of mathematics, and appreciation for culture. Implementation strategies include teacher training, development of culturally-based teaching materials, and collaboration between schools and communities. This approach also addresses the challenges of conventional mathematics instruction that is often abstract and less meaningful. Integrating ethnomathematics into the curriculum contributes to character development, cultural preservation, and the achievement of contextual and engaging learning.